Empirical analysis of the relationship between public expenditures and economic growth in Kazakhstan (Journal of Economic Research & Business Administration, 2024)
The relationship between fiscal policies and economic growth is one of the remarkable issues in the growth literature. In particular, the reasons for increasing public expenditures in countries and the effects of these increases on economic growth are important in the context of fiscal policy. Public expenditures are very important in terms of ensuring both political and economic stability in the economy. At this point, researchers examine whether public expenditures have increased in developed and developing countries from past to present. Some studies investigate the effects of public expenditures on economic growth with different approaches. There are many studies that support Wagner's and Keynes' approaches through cointegration and causality tests on the relationship between economic growth and government spending. The purpose of this study is to contribute to the literature by analyzing the asymmetric effects of economic growth on government spending in the short and long run within the nonlinear ARDL (NARDL) framework. The study used government spending and economic growth data for the period 1997-2021. According to the results of the empirical analysis, Wagner's law is valid in Kazakhstan, and economic growth has an asymmetric effect on public spending.Key words: public expenditures, economic growth, Kazakhstan, Wagner's law.